Optimising Drugs and Vaccines Management Utilizing 5 M Method: The Case of Riau Islands, Indonesia - Erwin Sutejo; Yosi Irawati Wibowo; Indri Ayu Ningsih; Bruce Sunderland; Adji Prayitno Setiadi (Faculty of Public Health, Hasanuddin University, Makassar, 2025)
A resilient health system should include the ability to access essential drugs and vaccines in all locations. This study aims to perform root cause analysis and develop recommendations to optimize drugs and vaccines management for Riau Islands Province, Indonesia. This study used qualitative approaches which included interviews and group discussions with key stakeholders (n=6) as well as an expert panel (n=4). Data on the underlying causes of problems and recommendations were structured into 5M (Man, Money, Machine, Method, Material). Problems related to Man (limited human resources) were identified for most management stages. Other problems reported: Planning – Money (inefficient budget management), Material (inaccurate data on local needs); Receival (unqualified delivery couriers); Storage - Machine (lack of infrastructure and cold chain assurance); Distribution – Material (urgent supply requests), Money (high cost of transportation), Machine (unqualified (cold chain) delivery couriers); Disposal – Machine (limited capacity); Documentation – Machine (unintegrated information system), and Material (mismatched data). Recommendations included improving human resources and budget management; improving infrastructure, especially to enhance cold chain assurance; scheduled distribution; and integrating the internal information system into the national system to provide real-time stock data. Findings from this study should provide a model for optimising pharmaceutical management in low-resource settings.